New data on the Avar Period chronology of the Körös–Tisza–Maros Interfluve - Bence Gulyás; Péter Somogyi; Gergely Szenthe (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae)
The study presents an analysis of the internal chronology of Szarvas-Grexa-téglagyár and Székkutas-Kápolnadűlő, two Avar cemeteries in the Trans-Tisza Region. According to a widely accepted theory, both were established only in the second half of the Avar Period. This dating could be re-evaluated based on the radiocarbon results presented here. The question of when the Middle Avar belt sets could have appeared in the region is also addressed in the study in connection with the internal chronology of the two sites.